2020
DOI: 10.1039/c9me00177h
|View full text |Cite
|
Sign up to set email alerts
|

Predicting selectivity of paracellular pores for biomimetic applications

Abstract: Systematic approach to predicting selectivity of paracellular pores for biomimetic applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 68 publications
2
7
0
Order By: Relevance
“…Indeed, computational works indicate the potential coexistence of the two pores in the same TJ strands. Coarse-grained MD simulations of self-assembly of Cldn protomers suggest diverse possible cis- dimers arrangements in the strand, all consistent with the units that construct the two pore configurations. ,, Furthermore, the same authors confirmed the formation of similar dimers using the PANEL software to obtain millions of Cldn–Cldn conformations and to analyze the amino acid contact maps. , The results showed the presence of both the Pore I and Pore II structures investigated in this work for Cldn5.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…Indeed, computational works indicate the potential coexistence of the two pores in the same TJ strands. Coarse-grained MD simulations of self-assembly of Cldn protomers suggest diverse possible cis- dimers arrangements in the strand, all consistent with the units that construct the two pore configurations. ,, Furthermore, the same authors confirmed the formation of similar dimers using the PANEL software to obtain millions of Cldn–Cldn conformations and to analyze the amino acid contact maps. , The results showed the presence of both the Pore I and Pore II structures investigated in this work for Cldn5.…”
Section: Resultssupporting
confidence: 77%
“…The MD simulations presented in ref demonstrate that the Cldn5 Pore II is impermeable to small molecules such as α-D glucose but permissive to water. However, at variance with Pore I, the Pore II model is still limitedly investigated, ,, and further studies are required to chart its structural and functional hallmarks. Moreover, a detailed investigation of its ionic permeability has not been performed yet, thus hampering a thorough comparison with Pore I.…”
Section: Introductionmentioning
confidence: 99%
“…A series of charged residues K31, K48, D65, E53, and Q63 from each claudin form the pore walls. 35 13.5 ± 0. water experiences a nominal barrier of 1.0 ± 0.01 kJ mol −1 toward the center of the pore, which is insignificant at physiological temperatures. The D65A mutation causes the barrier to increase to 1.9 ± 0.1 kJ mol −1 without adversely affecting the water permeability through the pore.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The pore is widest at the entrance (0.8 ± 0.1 nm) and narrowest in the middle (0.28 ± 0.08 nm), as shown in Figure b. A series of charged residues K31, K48, D65, E53, and Q63 from each claudin form the pore walls . Transport of water experiences a nominal barrier of 1.0 ± 0.01 kJ mol –1 toward the center of the pore, which is insignificant at physiological temperatures.…”
Section: Molecular Transport Through Claudin-2 Porementioning
confidence: 98%
“…Coarse grained MD simulations of self-assembly of Cldn protomers suggest diverse possible cis-dimers arrangements in the strand, all consistent with the units that construct the two pore configurations 34,35,40 . Furthermore, the same authors confirmed the formation of similar dimers using the PANEL software to obtain millions of Cldn-Cldn conformations and to analyze the amino acid contact maps 41,63 . The results showed the presence of both the Pore I and Pore II structures investigated in this work for Cldn5.…”
Section: Fe Calculationsmentioning
confidence: 81%